2010
DOI: 10.1016/j.ejpb.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in-line spatial filter velocimetry as PAT monitoring tool for particle growth during fluid bed granulation

Abstract: In this study, the feasibility of spatial filter velocimetry (SFV) as Process Analytical Technology tool for the in-line monitoring of the particle size distribution during top spray fluidized bed granulation was examined. The influence of several process (inlet air temperature during spraying and drying) and formulation variables (HPMC and Tween 20 concentration) upon the particle size distribution during processing, and the end product particle size distribution, tapped density and Hausner ratio was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 24 publications
0
34
0
7
Order By: Relevance
“…Particles passed through an aperture with 4 mm diameter and an internal (20 L/min) and external (3 L/min) pressurized air connection were used to disperse the particles and prevent fouling of the measurement zone by the moist product. The experimental set-up was optimized in a previous study, enabling representative size measurements without disturbing the process [5]. Measured raw data were collected via an A/D converter.…”
Section: Process Descriptionmentioning
confidence: 99%
“…Particles passed through an aperture with 4 mm diameter and an internal (20 L/min) and external (3 L/min) pressurized air connection were used to disperse the particles and prevent fouling of the measurement zone by the moist product. The experimental set-up was optimized in a previous study, enabling representative size measurements without disturbing the process [5]. Measured raw data were collected via an A/D converter.…”
Section: Process Descriptionmentioning
confidence: 99%
“…After restarting of liquid spraying (time point 165, figure 9c), the product temperature recovered rapidly to the average observation while not all fines could adhere to the larger granules. In a previous study, the influence of process and formulation variables upon the PSD of this formulation was studied in a DoE, which showed that the amount of HPMC had a positive effect upon granule size (Burggraeve et al, 2010). A possible action to prevent batch failure due to the large amount of fines, might for example be to spray more HPMC until the scores correspond to the average value.…”
Section: Real-time Batch Progress Evaluationmentioning
confidence: 99%
“…The software (In-line Particle Probe V7.12a) operated in the Windows XP environment. The experimental set-up and software settings were based on the knowledge of a previous study (Burggraeve et al, 2010). During the entire top-spray granulation processes, an average PSD was saved every 10 s and product temperature values were registered every minute.…”
Section: Fluid Bed Granulation Set-upmentioning
confidence: 99%
See 2 more Smart Citations